The Unknown Stalin - Medvedev, Roy Aleksandrovich, 1925- (I.B. Tauris, 2003)
Josef Stalin remains one of the greatest enigmas of modern history. Unflinching, impenetrable, inhuman in his cruelty, bathed in misery himself, he represents to many a very paradigm of evil - perhaps, in his icy rationalism, even more so than Hitler himself. More than a hundred biographies of Stalin have been written since his death in 1953, but this study looks at the torrent of new material unleashed with the opening of the secret Soviet archives when the Union collapsed. The truths extracted from these long-secret archives provide a radically fresh insight into the life and career of one o.